FAMILY EDUCATION MODEL BASED ON ISLAMIC VALUES IN THE KUA GUIDANCE PROGRAM - Arisman Juanda (Al-Mubin, 2025)
This study aims to examine and analyze the Islamic values-based family education model implemented in the Office of Religious Affairs (KUA) development program as an effort to maintain family integrity. The KUA plays a strategic role not only as a marriage administrative institution but also as an educational institution that provides guidance and counseling to the community in forming a harmonious, harmonious, and compassionate family. Through a qualitative approach with analytical descriptive methods, this study describes the KUA's strategy in organizing premarital education, family counseling, and postmarital guidance oriented towards Islamic values. The results show that the family education conducted by the KUA focuses on three main aspects: strengthening the faith as the foundation of family faith, fostering communal worship as a means of spiritualizing family relationships, and fostering morals as a moral foundation that fosters compassion, responsibility, and harmonious communication among family members. The program has been proven to have a positive impact in reducing the potential for domestic conflict and increasing awareness of married couples regarding the importance of religious values in family life. Thus, the KUA plays an important role as an agent of sustainable Islamic family education and development amidst modern social dynamics.